Effect of Solution Heat Treatment and Aging on the tensile Properties of Ti-6Al-4V Alloy Component Manufactured by Wire Arc Additive Manufacturing - Aniket Mitra; Dippayan Bouri; Harshadip Das; Sagar Kumar Mandal; Savan Kumar; Santu Majumder; Rittika Ghosh; Suraj Yadav; Kaushal Kishore; Srijan Paul; Sarnendu Paul (International Journal of Machine Systems and Manufacturing Technology, 2025)
Wire Arc Additive Manufacturing (WAAM) is a cost-effective technique for fabricating components from the Ti-6Al-4V alloy, known for its high strength and utility in demanding applications. To maximize its strength, the alloy undergoes Solution Treating and Aging heat treatment, comprising three key steps: (i) Solution Treating: The alloy is heated to 950°C (just below the β transus) and held for 1 hour, increasing the β phase proportion. This step sets the foundation for further strengthening in subsequent stages. (ii) Quenching: Rapid cooling in water preserves the β-favored phase from solution treatment. Without rapid cooling, the material would revert to a higher α phase content upon slow cooling. However, this quenching process can introduce residual stresses and unstable structures, like martensite. (iii) Aging: The alloy is held at 530°C for 8 hours, decomposing residual martensite and unstable β phase into stable α and β phases. This controlled transformation enhances the alloy's mechanical strength, by up to 3.13%.
Keywords: Solution Treatment and Aging (STA); Ti-6Al-4V; WAAM; tensile properties